RASIO PASAR DAN HARGA SAHAM DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Herlina Wati, Pebri; Ratna Sari, Maria M. (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
The study intends to determine the effect of the ratio of the market price of the stock. The number of samples was 51 companies, with a purposive sampling method. Linear regression was used as analysis techniques. Data analysis showed that all independent variables simultaneously, ie EPS, DPS, DPR, DY, PER and PBV significant effect on stock prices. Partially, EPS, DPS, DPR, PER and PBV had significant effect on stock prices fluctuation, while DY insignificant effect on stock  prices. That is, EPS, DPS, DPR, DY, PER and PBV affect the fluctuation of  stock prices, but the size of the DY did not significantly affect stock prices fluctuation.
Keywords: market ratio, stock prices, indonesian stock exchange